Influence of Perceived Information-Sharing Norms on Communication Channel Utilization - Dewhirst, H. Dudley (Academy of Management Journal, 1971)
Research on communication channel use has shown that interpersonal channels are generally more efficient than written channels. However, using interpersonal channels involves a psychological cost, particularly for individuals who believe that free and open sharing of information is not the norm. This study explores channel use among a group of scientists and engineers. It suggests that channel use, both within and outside the organization, is influenced by the individuals' perceptions of organizational information-sharing norms.